Hyperhidrosis prevalence and its impact on population - Hasimoto, Erica Nishida [UNESP]; Cataneo, Daniele Cristina [UNESP]; dos Reis, Tarcisio Albertin [UNESP]; Cataneo, Antonio José Maria [UNESP] (AME Publishing Company, 2019)
Hyperhidrosis is a disorder characterized by excessive sweating which beyond the physiological need for body thermoregulation. It brings about a deep social, psychic, professional and emotional constraint, compromising the quality of life of its patients. The prevalence data available in the literature are practically nonexistent up to the beginning of the 21st century. The objective of this present study is to review the literature as a quest for studies that evaluated the prevalence of hyperhidrosis and its impact on the quality of life of individuals. The bibliographic review was carried out by using the PubMed database. During the search 16 articles were found which evaluated the prevalence of hyperhidrosis and out of these, 5 evaluated the impact in the disorder as to the quality of life. The prevalence found in the articles varied from 0.072% to 16.3%. As to the impact on the quality of life, all articles have shown that such disorder affects in some way the life of the individuals. Although the methodology is quite different among the studies and though some prevalence data are questionable, the undertaking of this kind of study is important for the scaling of the problem and the establishment of measures that seek the improvement of the quality of life of its patients.
Keywords: Hyperhidrosis; Prevalence; Quality of life